SUSTAINABLE AGRICULTURE: A CASE STUDY ON THE PALM OIL INDUSTRY - S, Aikanathan; S, Chenayah; A, Sasekumar (Malaysian Journal of Science, 2011)
The palm oil industry has long suffered criticism for destroying forest, wildlife and denying rightful ownership of land. To avert these persisting criticisms, the Roundtable on Sustainable Palm Oil (RSPO) was formed by a diverse group of stakeholders in the palm oil industry, to promote sustainable agriculture and address environment impact. Sustainability efforts begin from good environmental, social and agricultural practices: where the oil palm is first planted and grown to it final destination, the plate of a consumer or other products. The palm oil industry is the first to have certified sustainable produce, through the RSPO certification. The sustainability measurements are based on RSPO‟s 8 principles, 39 criteria, 126 indicators and guidance. The formation of the RSPO has not been without criticism from various sectors, especially the environmental NGOs. Sustainability in agricultural practises is no more an option, and agriculture need to feed the growing billions in the earth‟s population. The ever degrading environment needs protection and restoration. But, we can afford to fail with or without RSPO and other efforts by the industry similar to Malaysian Palm and Indonesian Sustainable Palm Oil should be given encouragement and support. (Key Words: Agriculture, Palm Oil, Sustainable, Small Farmers, Life Cycle)